Konseling Individu Terhadap Siswa Korban Broken Home (Studi Kasus Di SMA Negeri 2 Kota Padangsidimpuan) - Riem Malini Pane (IAIN Padangsidimpuan, 2020)
The problem in this study is how to carry out individual counseling in dealing with broken home victims in SMA Negeri 2 Padangsidimpuan City, what method is used in dealing with broken home victims in SMA Negeri 2 Padangsidimpuan City, why is individual counseling used to deal with broken home victims at SMA Negeri 2 Padangsidimpuan City Based on the above problems, the purpose of this study was to find out the description of the implementation of individual counseling in dealing with broken home victims in SMA Negeri 2 Padangsidimpuan City, to find out the method used in dealing with broken home victims at SMA Negeri 2 Padangsidimpuan City, and to find out the use of individual counseling in dealing with broken home victims in SMA Negeri 2 Padangsidimpuan City. This type of research is qualitative, namely research conducted by observing the surrounding phenomena and analyzing them using scientific logic. The approach used in qualitative research is to use a descriptive qualitative approach, aims to describe systematically and accurately, certain facts and characteristics. Based on this research, it was found that the implementation of individual counseling in dealing with broken home victims in SMA Negeri 2 Padangsidimpuan City not well structured but the BK teacher himself took the initiative to solve student problems by meeting the homeroom teacher not well structured but the BK teacher himself took the initiative to solve student problems by meeting the homeroom teacher is student acceptance regardless of condition, carrying out assessment of student problems, is empathy and sympathy for students, listening and giving open questions to students, the method used in dealing with broken home victims at SMA Negeri 2 Padangsidimpuan City is directive counseling services provided by the BK teacher to handle the case of students from broken home families in SMA Negeri 2 Padangsidimpuan City is in the form of individual counseling, because it is considered more effective, consideration that student problems are classified as personal problems, also more open students express their problems